Sequestration of Stigmasterol and β-Sitosterol from Ethanolic Extract of Kam Sabut (Croton caudatus Geiseler) Leaves - Shantabi, Longjam; Chandra Jagetia, Ganesh; Victoria Devi, Sharubam; Lalhenmawia, H.; H. Gaonkar, Raghuvir (Asian Journal of Chemistry, 2021)
Croton caudatus (Kam sabut) has been traditionally used to treat cancer in northeastern India and earlier studies reported the anticancer activity of ethanolic extract of C. caudatus leaves in HeLa cells in vitro and Swiss albino mice transplanted with Dalton’s ascites lymphoma. Therefore, isolation of stigmasterol and β-sitosterol from the ethanolic extract of C. caudatus Geiseler leaves was carried out. Stigmasterol and β-sitosterol were isolated from the ethanolic extract of dried leaves of C. caudatus by column chromatography. The fractions were purified further on Sephadex® LH-20 column chromatography and reverse-phase HPLC. The isolated phytosterols were characterized and quantified by IR, 1H & 13C NMR, mass spectroscopy and HPLC. This has led to the separation of 100 mg stigmasterol and 80 mg β-sitosterol. Stigmasterol and β-sitosterol have been isolated from the ethanolic extract of C. caudatus leaves for the first time.